Driver compliance with the 2022 UK highway code rule on giving way to pedestrians at side roads: A naturalistic observation study - Sarah E. O’Toole; Nicola Christie; Damian Poulter (Journal of Urban Mobility)
The 2022 update to the UK Highway Code introduced a new H2 rule granting pedestrians right of way at side road junctions. However, the communication campaign for this change was limited and there has yet to be a systematic evaluation of driver compliance. This study therefore involved a naturalistic observation of driver yielding behaviour when turning from a main road into a side road. A total of 809 driver-pedestrian interactions were observed to assess compliance with the rule, alongside driver, vehicle, pedestrian, and environmental characteristics. Results indicated that only 31 % of drivers complied with the rule when turning from a main road into a side road where pedestrians were approaching or waiting at a junction to cross. However, female drivers and taxi drivers were more likely to yield to pedestrians at junctions. Further, compliance was greater when there was a group of pedestrians opposed to a single pedestrian or when it was early afternoon. These findings suggest further interventions may be necessary to enhance adherence and improve pedestrian safety.